A pilot study examining the impact of aphasia camp participation on quality of life for people with aphasia. Issue 2 (17th February 2017) - Kim, Esther S.; Ruelling, Andrea; Garcia, J. Renzo; Kajner, Rhonda
Abstract : Objectives: For people with aphasia (PWA), attending an aphasia camp can result in increased confidence, social relationships, and greater participation in activities. Although much anecdotal evidence of the benefits of aphasia camps exists, systematic studies on outcomes from aphasia camp participation are lacking. The purpose of this pilot study was to examine the effect of attending the Alberta Aphasia Camp on quality of life for people with aphasia. Methods: Nine PWA who attended the inaugural Alberta Aphasia Camp completed the Assessment for Living with Aphasia - 2 before and after camp. A subset of their caregivers ( n = 4) completed the Communicative Effectiveness Index, a rating scale evaluating their PWA's communication, and were interviewed about their experiences and perceptions of camp participation. Results: Significant changes were observed on total scores on the ALA - 2, and in particular the Personal and Participation subtests. These improvements were corroborated by themes identified from interviews with caregivers. Discussion: This study provides preliminary evidence that aphasia camp participation can result in improved outcomes for PWA across a range of domains. Aphasia camps provide a unique intervention for PWA and caregivers to experience therapeutic and recreational activities, respite and create social connections in a supported communication environment. Future studies should recruit a greater number of participants, employ control groups, and examine outcomes for caregivers.